Carel Breytspraak Sr., Purveyor to his Majesty King Louis Napoleon. Breytspraak furniture from the collection of the Royal Palace in Amsterdam (Bulletin KNOB, 2013)
In 1808, King Louis Napoleon had the town hall of Amsterdam converted to Royal Palace. Besides making the necessary architectural alterations, he ordered hundreds of pieces of furniture and other ornamental objects from local furniture makers, upholsterers, decorators and other suppliers. This collection of Empire furniture, which is still preserved in the palace, is today the largest of its kind outside France. Between 2005 and 2009, these pieces of furniture were restored as part of the wider restoration of the entire palace, a gigantic operation that involved hundreds of restoration experts. A furniture committee made sure that quality and looks remained uniform. During the process the restoration experts and researchers made a full study of the furniture, documenting finds and findings, supplemented with research into the origins, the makers, use, techniques and material. This is unique for the Netherlands. The data, recorded in documentation and restoration reports, offer fresh insights in especially the construction and manufacturing process of Dutch Empire furniture.The discoveries are illustrated by a number of purveyances by Carel Breytspraak Sr. (1769-1810), the best paid furniture maker of the king. The 100 chairs he made for the Grand dining room of the palace are an example of pre-modern serial production. This may be inferred from the varying quality of the wood that was used and from the varying thickness of the seat stretchers, among other things. Furthermore, it turned out that the chairs still had the original stuffing, which was reused after having been restored. One chair still had the original upholstery from the days of Louis Napoleon and this was used as the basis for the current upholstery. The chairs are typical examples of furniture made after French decoration prints, which were undoubtedly provided by the king’s architects.The roll-top desk that Breytspraak made for the king’s bedroom is one of the most unique pieces in the collection and is certainly not a mass product. Unlike with the chairs, the mahogany wood used here – mainly applied in mirrored fashion – is of a strikingly high quality. The desk is an example of previous restoration or maintenance efforts. For instance, the marble top as well as the fittings on the lower doors turned out not to be original. This has been remedied in this restoration campaign.Another set of furniture that suffered from previous activities is the corps de bibliothèque. A special aspect here is that for these bookcases – intended for the king’s library and topographical collection – we still have the contract between Breytspraak and the architect, which gives us insight into how the furniture maker was instructed. What is interesting is that Breytspraak was ordered to construct the bookcases in such a way that the shelves could be moved. He was also especially requested to give them a mahogany finish, in such a way that they would have the appearance of massive mahogany.Finally, some small pieces of furniture for the apartment of the crown prince (1809) demonstrate the versatility of Breytspraaks workshop. He produced several gueridons (tripod tables), constructed from a ‘wagon wheel’ carrying a marble top, with a column and a plinth on lion’s feet. These elements are fixed with an iron rod that can be tightened. Further research could provide more insight into the production process and the differences between the Dutch and French furniture.